Analysis of Employee Engagement at PT KAI Daop 8 Surabaya in Terms of Workload and Work-Life Balance - Situmeang, Angelica Br; Iryanti, Endang (CV. Lenggogeni Data Publishing, 2025)
This study aims to examine the effect of workload and work-life balance on employee engagement at PT KAI Daop 8 Surabaya. The study was prompted by the importance of employee engagement in supporting organisational performance, which can be influenced by high workloads and the ability to maintain a balance between work and personal life. A quantitative approach was used in this study, employing a survey method. Data was collected by distributing questionnaires to 96 employees selected using simple random sampling. The data analysis method used in this study was Partial Least Squares (PLS) analysis to test validity, reliability, and hypotheses. The results revealed that workload had a negative effect, while work-life balance had a positive effect on employee engagement. Simultaneously, both variables had a significant effect on employee engagement. These findings emphasise the need for proportional workload management and the strengthening of work-life balance programmes to improve employee engagement and performance.